IMPLEMENTASI MODEL EVALUASI PENDIDIKAN INTEGRATIF DI MADRASAH IBTIDAIYAH: STUDI KASUS MI AL-MUJTAHIDIN PADALARANG - Ani sumarni; Mulyawan Safwandy Nugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of an integrated educational evaluation model combining formative–summative assessment, the CIPP (Context, Input, Process, Product) model, outcome-based evaluation, and a participatory approach at Madrasah Ibtidaiyah Al-Mujtahidin Padalarang. The research is grounded in the growing need for comprehensive evaluation practices that not only measure learning outcomes but also improve the quality of educational processes and stakeholder engagement. The objective of this study is to explore how these evaluation models are applied in practice and how they contribute to school improvement. A qualitative case study design was employed, involving interviews, observations, and document analysis with teachers, school leaders, and community representatives. The findings reveal that formative and summative evaluations are used in a complementary manner to monitor student progress, while the CIPP framework helps guide institutional decision-making. The outcome-based approach ensures alignment between learning objectives and results, and the participatory approach strengthens collaboration among stakeholders. In addition, the integration of these models encourages reflective practices among teachers and supports more adaptive instructional strategies in response to student needs. However, challenges were identified in terms of consistency, teacher readiness, and limited evaluation training. The study concludes that integrating multiple evaluation models can enhance the effectiveness of educational assessment when supported by continuous professional development and institutional commitment. This approach offers a practical framework for improving both learning quality and school governance in similar educational settings.